2009
DOI: 10.1539/joh.l8071
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion of Health Education Programs with Reference to Health Behavior Theories in Japanese Workplaces: Present Status and Future Plans

Abstract: Diffusion of Health Education Programs with Reference to Health Behavior Theories inThe study surveyed 1,372 companies with 500 or more employees. In a cross-sectional study, the characteristics of the health education programs were surveyed using a questionnaire, which included items regarding target lifestyle-related diseases and lifestyle areas, and the health behavior theories used to develop the present status and future plans. Results: One hundred ninety companies responded giving a response rate of 13.8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 15 publications
(15 reference statements)
0
2
0
Order By: Relevance
“…People should be encouraged to maintain desirable lifestyle habits and become self-reliant over the long-term (Wing and Phelan, 2005). Intervention programs that include health behavior theories (Prochaska et al, 1992;Johnson et al, 2008), social cognitive theory (Bandura, 2001), and other theories based on behavioral sciences (Kaplan et al, 1977), have been suggested to be effective (Fujii and Muto, 2009). However, few studies have examined the results of health promotion programs in Japanese white-collar workers, prompting us to design this randomized controlled trial.…”
Section: Introductionmentioning
confidence: 99%
“…People should be encouraged to maintain desirable lifestyle habits and become self-reliant over the long-term (Wing and Phelan, 2005). Intervention programs that include health behavior theories (Prochaska et al, 1992;Johnson et al, 2008), social cognitive theory (Bandura, 2001), and other theories based on behavioral sciences (Kaplan et al, 1977), have been suggested to be effective (Fujii and Muto, 2009). However, few studies have examined the results of health promotion programs in Japanese white-collar workers, prompting us to design this randomized controlled trial.…”
Section: Introductionmentioning
confidence: 99%
“…A definition of occupational health management (OHM) was given in the declaration of occupational health in the European Union 1997 [8]. implemented in many companies to improve health and reduce absenteeism [11,31].…”
Section: Introductionmentioning
confidence: 99%